CSU Channel Islands Osher Lifelong Learning Institute: Member Satisfaction Survey Report, 2011 - Betterley, Annie; Betita, Richard; Pipkin, Scott; Ruvalcaba, Jeanette; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
The research was conducted with and on behalf of the Osher Lifelong Learning Institute (OLLI) at CSU Channel Islands to identify and measure levels of satisfaction among members (students). It is based on a concurrent survey of both current and former members of OLLI. Of the total surveys we collected (N = 208), 152 were completed by current members and 56 by former members, during the last two weeks of March 2011. Findings are presented in the following areas: member demographics; member characteristics; preferences regarding class offerings; member satisfaction; and member preferences regarding social events.